The idea is that C(n,k) = C(n-1, k-1) U n + C(n-1,k), do you get this?

```
class Solution {
public:
vector<vector<int> > combine(int n, int k) {
vector<vector<int> > result;
if (n < 1 || k <1 || k > n)
{
return result;
}
result = combine(n-1, k-1);
if(result.empty())
{
result.push_back(vector<int>{n});
}
else
{
for (vector<vector<int> >::iterator it = result.begin();
it!= result.end(); it++)
{
it->push_back(n);
}
}
vector<vector<int> > result2 = combine(n-1, k);
result. insert(result.end(), result2.begin(), result2.end());
return result;
}
};
```